Prognostic significance of high circulating sHLA‐G in ovarian carcinoma. (26th July 2021) - Babay, Wafa; Boujelbene, Nadia; Ben Yahia, Hamza; Bortolotti, Daria; Zemni, Ines; Ouzari, Hadda‐Imene; Chelbi, Hanene; Mezlini, Amel; Rizzo, Roberta; Zidi, Inès
Abstract : HLA‐G is a non‐classical major histocompatibility complex class Ib molecule. Its expression has been described in various cancer types, including ovarian cancer. HLA‐G molecule has been implicated in immune escape and in progression of ovarian tumor cells. Our goal was to assess if total soluble (s)HLA‐G molecules or HLA‐G5 and sHLA‐G1 isoforms could be considered as circulating ovarian tumor biomarkers, we measured the concentration of these molecules in ovarian carcinoma patients stratified according with their clinicopathological parameters. sHLA‐G, sHLA‐G1 and HLA‐G5 concentrations were dosed in plasma samples by sandwich‐ELISA. The sHLA‐G dimerization was analyzed after immunoprecipitation and SDS‐PAGE migration. Total sHLA‐G and sHLA‐G1 levels were significantly represented in plasma of ovarian carcinoma patients compared to healthy controls. sHLA‐G1 isoform concentration was highly represented in ovarian carcinoma compared to HLA‐G5 isoforms. Additionally, high sHLA‐G molecules have been found in aged patients, as well as in patients with advanced stages, and those with metastatic lymph nodes and those with distant metastasis. Elsewhere, sHLA‐G monomers were highly represented in ovarian carcinoma patients compared to controls. sHLA‐G plasmatic protein was highly represented in ovarian carcinoma. In effect, HLA‐G might be considered as a new checkpoint molecule that could be used to assess progression and recurrence of the disease, thus placing it as a potential biomarker for advanced and complicated ovarian carcinoma.